2021
DOI: 10.3389/fendo.2021.738895
|View full text |Cite
|
Sign up to set email alerts
|

The Negative Impacts of Acromegaly on Bone Microstructure Not Fully Reversible

Abstract: PurposeThis study aimed to evaluate the bone turnover markers and bone microarchitecture parameters derived from high-resolution peripheral quantitative computed tomography (HR-pQCT) in active and controlled acromegaly patients.MethodsThis cross-sectional study involved 55 acromegaly patients from a tertiary hospital (23 males and 32 females, aged 45.0 ± 11.6 years). Firstly, growth hormone (GH), insulin-like growth factor-1 (IGF-1), and markers for bone turnover were assessed. Next, we derived peripheral bone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 29 publications
2
9
0
Order By: Relevance
“…This suggests that, despite their possible greater exposure of bone to GH/IGF-1 excess, the pegvisomant-treated patients had similarly persistently impaired but no worse bone quality. The fact that pegvisomant-treated patients compared similarly to the remission and active disease comparison groups is consistent with prior studies showing that microstructural abnormalities do not vary with disease activity in surgically treated patients [ 10 , 41 ]. Although in a recent longitudinal HRpQCT study we found improved but persistent deficits in volumetric density and microarchitecture, Stiffness, and F.load in a group of acromegaly treated successfully with surgery or SRL therapy [ 10 ], the current cross-sectional study cannot determine if partial improvements also occurred with initiation of pegvisomant therapy.…”
Section: Discussionsupporting
confidence: 88%
“…This suggests that, despite their possible greater exposure of bone to GH/IGF-1 excess, the pegvisomant-treated patients had similarly persistently impaired but no worse bone quality. The fact that pegvisomant-treated patients compared similarly to the remission and active disease comparison groups is consistent with prior studies showing that microstructural abnormalities do not vary with disease activity in surgically treated patients [ 10 , 41 ]. Although in a recent longitudinal HRpQCT study we found improved but persistent deficits in volumetric density and microarchitecture, Stiffness, and F.load in a group of acromegaly treated successfully with surgery or SRL therapy [ 10 ], the current cross-sectional study cannot determine if partial improvements also occurred with initiation of pegvisomant therapy.…”
Section: Discussionsupporting
confidence: 88%
“…The early onset and the irreversibility of VFs requires strict screening and surveillance protocols since the time of acromegaly diagnosis [ 38 , 39 ], that includes the assay of markers of bone formation and resorption, calcium, vitamin D and parathyroid hormone (PTH), the vertebral morphometry and possibly the analysis of bone microstructure though the trabecular bone score (TBS) and the microindentation technique [ 40 ]. In addition, the vitamin D supplementation and the prescription of bone active drugs may improve the bone quality in acromegaly patients, in particular in those with active disease, together with the early normalization of GH and IGF-1 levels [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Patients with active acromegaly have been shown to be at higher risk of vertebral fractures compared to those with a controlled/cured disease [5]. However, in a recent HR-pQCT study, Duan et al [53] suggested that the negative impact of acromegaly on bone microstructure may still not be fully reversible. With respect to TBS values, our meta-analysis could not highlight any significant difference in the outcome measure according to acromegaly disease activity.…”
Section: Discussionmentioning
confidence: 99%